What factors enable sustainable university-industry collaboration communities? Evidence from a symbiosis theory perspective - Jun Liu; Xuewei Wang; Wenqing Miao; Xiurong Wang (Sustainable Futures)
With the acceleration of global technological revolution and industrial transformation, the integration of industry and education has emerged as a critical focus in the educational sphere. The University-Industry Collaboration (UIC) community, as a multi-stakeholder collaborative mechanism, emphasizes cooperation among government entities, higher education institutions, and enterprises to promote resource sharing and talent cultivation. However, in practice, the collaboration between universities and enterprises still faces numerous challenges, particularly in aspects of collaborative governance and interest coordination. Through grounded theory methodology, this study explores the roles of symbiotic mechanisms, symbiotic subjects, and symbiotic environments in constructing UIC communities, ultimately developing an influencing factors model. The findings indicate that symbiotic mechanisms—including resource coordination, information communication, interest alignment, and organizational support—directly impact community construction. Additionally, the collaborative efforts among universities, enterprises, government bodies, industry associations, and students, along with environmental factors such as economic development, sociocultural conditions, technological innovation, and policy frameworks, play crucial roles in advancing the deep integration of industry and education. This research provides both theoretical foundations and practical guidance for promoting the construction of University-Industry Collaboration (UIC) communities. • University-Industry Collaboration (UIC) faces challenges in implementation, including communication barriers between institutions and misaligned expectations between stakeholders • Traditional approaches to university-enterprise cooperation often lack systematic frameworks for sustainable collaboration and resource sharing • The success of industry-education partnerships heavily depends on institutional support and policy frameworks, but practical guidelines for implementation are often unclear • Introduces a comprehensive ''three-dimensional symbiosis'' framework that provides practical guidance for establishing and maintaining effective industry-education partnerships • Identifies specific mechanisms for successful collaboration, including resource sharing, information exchange, interest alignment, and organizational support structures • Presents evidence-based strategies for overcoming common barriers in University-Industry Collaboration (UIC), based on systematic analysis of real-world implementations • Educational institutions should establish dedicated communication channels and resource-sharing platforms to facilitate ongoing collaboration with industry partners • Policy makers need to develop targeted incentive mechanisms and clear evaluation criteria to encourage sustained participation from both educational institutions and industry partners • Practitioners should focus on building long-term relationships through structured programs that address both immediate needs and strategic development goals of all stakeholders